The Politics of Poverty Reduction Strategy Papers - Amir Saeed; Mehmood ul Hassan; Ghalib Atta & Qurrat ul Ain Qazi (Journal of Political Studies, 2015)
This paper offers a critique on the politics of the Poverty Reduction Strategy Papers and their framework, processes, and content. The paper challenges the fundamental assumptions of the poverty reduction approach and the underlying politics of the international financial institutions with a view to seek the answer to question as to why the development programmes initiated under the auspices of the World Bank and IMF failed to address the issue of poverty in the developing countries, especially in Pakistan. The ontological and epistemological basis of poverty as defined in poverty reduction strategies are of a special interest. The paper focuses on measures such as trade liberalization, free market and privatization of public sector institutions, suggested as remedies to treat the menace of widespread poverty, and reviews the min the backdrop of Western cultural ideals such as political liberalism, the instrumental conception of social action and value neutrality of scientific knowledge.